Pengaruh Budaya Organisasi Terhadap Kinerja GuruDi Madrasah Aliyah Negeri 2 Pekanbaru - harwina, yulia (Sekolah Tinggi Ilmu Ekonomi Riau, 2024)
This research was conducted at Madrasah Aliyah Negeri (MAN) 2 Pekanbaru. The purpose of this study was to determine the effect of organizational culture on teacher performance at Madrasah Aliyah Negeri (MAN) 2 Pekanbaru. The population in this study were 77 people. In this study, the sample was taken using a census technique, namely 77 people. The data used are primary and secondary data with analysis using simple linear regression with the result of the equation Y = 17.062 + 0.672X. The results showed that the t_count > t_table (5.741> 2.0210) and the Sig. smaller than 0.05 so it can be concluded that there is a significant influence between organizational culture on teacher performance at Madrasah Aliyah Negeri (MAN) 2 Pekanbaru. The results of the coefficient of determination obtained the R_square value or the coefficient of determination of 0.452 which means that the influence of the independent variable on the dependent variable is 45.2 percent while the remaining 54.8 percent is influenced by other independent variables not observed in this study, such as compensation, environment work, and others.